2017
DOI: 10.2147/jep.s124391
|View full text |Cite
|
Sign up to set email alerts
|

Review about gabapentin misuse, interactions, contraindications and side effects

Abstract: The current work is targeted to review the risks of gabapentin misuse, its potential interactions with other drugs, side effects and use contraindications. This review consists of a total of 99 biographical references (from the year 1983 to 2016). A publication search of PubMed was performed from January 1983 to December 2016. It included animal studies, clinical studies, case studies and reviews related to gabapentin misuse, potential interactions, side effects and use contraindications. The search terms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 82 publications
0
57
0
3
Order By: Relevance
“…Over the past 5 years, however, several studies have begun to provide evidence of the mechanisms underlying unintended consequences associated with gabapentinoid use both individually and in combination with opioids. Common side effects associated with gabapentinoids include dizziness, euphoria, somnolence, and gait disturbances [26][27][28]. One study [29] reported the patterns of gabapentin abuse and overdose were similar to those of other medications with known misuse risks, and some patients were prescribed daily doses that exceeded FDA recommendations by threefold [11].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 5 years, however, several studies have begun to provide evidence of the mechanisms underlying unintended consequences associated with gabapentinoid use both individually and in combination with opioids. Common side effects associated with gabapentinoids include dizziness, euphoria, somnolence, and gait disturbances [26][27][28]. One study [29] reported the patterns of gabapentin abuse and overdose were similar to those of other medications with known misuse risks, and some patients were prescribed daily doses that exceeded FDA recommendations by threefold [11].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with the other medications used to treat neuropathic pain such as carbamazepine, valproic acid, and amytriptyline, gabapentin has been historically recognized to be well tolerated in general with a relatively mild side- [16,17]. Side effects that have been reported for gabapentin include: somnolence, dizziness, ataxia, fatigue, diarrhea, hypoventilation, visual field deficits, and sexual dysfunction [30,31]. There are also reports of misusing and abusing gabapentin in up to 15% of patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…Side effects that have been reported for gabapentin include: somnolence, dizziness, ataxia, fatigue, diarrhea, hypoventilation, visual field deficits, and sexual dysfunction [30,31]. There are also reports of misusing and abusing gabapentin in up to 15% of patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…nen Erkrankungen wurden bisher keine sicheren Abhängigkeitsfälle durch diese Substanzen berichtet [3, 55,[70][71][72][73][74].…”
Section: üBerdosierungenunclassified